2010
DOI: 10.1111/j.1365-2966.2009.15846.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical variability of radio-intermediate quasars

Abstract: We report the results of our intensive intranight optical monitoring of 8 `radio-intermediate quasars' (RIQs) having flat or inverted radio spectra. The monitoring was carried out in {\it R-} band on 25 nights during 2005-09. An intranight optical variability (INOV) detection threshold of $\sim$ 1--2% was achieved for the densely sampled differential light curves (DLCs). These observations amount to a large increase over those reported hitherto for this rare and sparsely studied class of quasars which can, how… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 94 publications
(241 reference statements)
2
19
0
Order By: Relevance
“…Over the past two decades there have been rather extensive searches for this phenomenon in blazars, other types of radio‐loud quasi‐stellar objects (RLQSOs) and the far more numerous radio‐quiet quasars (RQQSOs) (e.g. Miller, Carini & Goodrich 1989; Carini et al 1992, Carini et al 2007; Gopal‐Krishna, Wiita & Altieri 1993b; de Diego et al 1998; Romero, Cellone & Combi 1999; Gopal‐Krishna et al 2000, 2003; Sagar et al 2004; Stalin et al 2004; Montagni et al 2006; Goyal et al 2010). In the case of blazars these studies have provided useful constraints on the relativistic jet based models that are used to explain the origin of the large variations that help define the category (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades there have been rather extensive searches for this phenomenon in blazars, other types of radio‐loud quasi‐stellar objects (RLQSOs) and the far more numerous radio‐quiet quasars (RQQSOs) (e.g. Miller, Carini & Goodrich 1989; Carini et al 1992, Carini et al 2007; Gopal‐Krishna, Wiita & Altieri 1993b; de Diego et al 1998; Romero, Cellone & Combi 1999; Gopal‐Krishna et al 2000, 2003; Sagar et al 2004; Stalin et al 2004; Montagni et al 2006; Goyal et al 2010). In the case of blazars these studies have provided useful constraints on the relativistic jet based models that are used to explain the origin of the large variations that help define the category (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of intranight optical variability (INOV), or microvariability, among quasars, particularly their more active subset called blazars, is now well documented in the literature (e.g., Miller et al 1989;Jang & Miller 1995Romero et al 1997Romero et al , 2002Gopal-Krishna et al 2003Sagar et al 2004;Stalin et al 2004aStalin et al ,b, 2005Gupta et al 2005Gupta et al , 2008Rani et al 2010;Goyal et al 2010). Considerable uncertainty persists, however, about the underlying physical mechanism and even from a purely observational perspective contrasting claims have been made (reviewed, e.g., by Wiita 2006;Wagner & Witzel 1995).…”
Section: Introductionmentioning
confidence: 99%
“…(c) In order to augment the sample, we included all 3 CDQs from the sample of Sagar et al (2004), for which Wills et al (1992) give P op < 2 per cent. These LPCDQs are J0958+3224, J1131+3114 and J1228+3128; J1312+3515 was not included as it is a radio-intermediate quasar (Goyal et al 2010). The intranight lightcurves for these 3 LPCDQs are taken from the study by Sagar et al (2004) which belongs to the first part of our INOV programme.…”
Section: The Lpcdq Samplementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, based on rapid radio flux variability, relativistically beamed jets are inferred to be common among RIQs (Wang et al 2006). However, a study of the optical variability of RIQs on hour to day-like time scales, based on intranight monitoring of 10 RIQs on 42 nights, has shown that while intra-night and inter-night optical variability is exhibited by RIQs, the INOV amplitude hardly ever exceeds 3 − 4%, in clear contrast to blazars (Goyal et al 2010). This is consistent with the inference that a relativistically beamed radio core of a quasar is not a sufficient condition for observing a pronounced INOV (Goyal et al 2012).…”
Section: Remarks On Possible Inov Eventsmentioning
confidence: 99%